2019
DOI: 10.1371/journal.pone.0208614
|View full text |Cite
|
Sign up to set email alerts
|

Imputation accuracy of wheat genotyping-by-sequencing (GBS) data using barley and wheat genome references

Abstract: Genotyping-by-sequencing (GBS) provides high SNP coverage and has recently emerged as a popular technology for genetic and breeding applications in bread wheat (Triticum aestivum L.) and many other plant species. Although GBS can discover millions of SNPs, a high rate of missing data is a major concern for many applications. Accurate imputation of those missing data can significantly improve the utility of GBS data. This study compared imputation accuracies among four genome references including three wheat re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 68 publications
(76 reference statements)
3
41
0
Order By: Relevance
“…Dubcovsky and Dvorak (2007) reported the hexaploid wheat was found to have a larger portion of the natural gene diversity from its tetraploid ancestor (AABB) than the diversity found in the Aegilops tauschii (DD). Similarly, the identification of a relatively higher frequency of SNPs showing transition substitutions (62.3%) than transversions is consistent with previous genome-wide SNP discovery studies in crop plants, including wheat (Parida et al, 2012;Lai et al, 2015;Rimbert et al, 2018;Alipour et al, 2019). The present study showed that the GBS-derived SNPs hold potential variation among genomes, which has to be explored further by analyzing the genomic variation of Triticum genotypes.…”
Section: Genotyping Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…Dubcovsky and Dvorak (2007) reported the hexaploid wheat was found to have a larger portion of the natural gene diversity from its tetraploid ancestor (AABB) than the diversity found in the Aegilops tauschii (DD). Similarly, the identification of a relatively higher frequency of SNPs showing transition substitutions (62.3%) than transversions is consistent with previous genome-wide SNP discovery studies in crop plants, including wheat (Parida et al, 2012;Lai et al, 2015;Rimbert et al, 2018;Alipour et al, 2019). The present study showed that the GBS-derived SNPs hold potential variation among genomes, which has to be explored further by analyzing the genomic variation of Triticum genotypes.…”
Section: Genotyping Assaysupporting
confidence: 91%
“…(Wong et al, 2015;Edet et al, 2018). Various studies reported the impact of missing datasets on phylogenetic analyses (Philippe et al, 2004;Xi et al, 2015) and concluded that the missing data can be addressed with a statistical method (Alipour et al, 2019;Schurz et al, 2019). Therefore, to explore further the utility of missing SNP datasets on phylogenetic analysis, we employed missing rates of 20, 50, and 80%, which revealed that decreasing the missing rates leads to reduction of SNPs.…”
Section: Genotyping Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…We used the genotyping-by-sequencing (GBS) [ 32 ] method for genetic fingerprinting and Poland et al [ 33 ] method for library construction. The genotyping method has been described for the association panel, previously [ 34 , 35 ]. Briefly, DNA was extracted by a modified cetyltrimethylammonium bromide (CTAB) method [ 36 ] and double-digested with PstI and MspI restriction enzymes, barcoded adapters were ligated to each DNA sample using T4 ligase, polymerase chain reactions (PCRs) were done using primers complementary to both adaptors, size-selection for 250–300 bp fragments was conducted using an E-gel system (Life Technologies, Inc.), and the size-selected library was sequenced on an Ion Proton sequencer (Life Technologies, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…After specifying the haplotype phase for all individuals, the data was subjected to imputation using BEAGLE v3.3.2 [71] based on available allele frequencies obtained. During imputation, four different reference genomes were assessed that among them W7984 reference genome was shown to have the greatest imputation accuracy [72]. The different chromosomes LD decay was obtained using the ggplot2 package in RStudio [73] based on LOESS regression.…”
Section: Genotyping By Sequencing and Imputation Methodsmentioning
confidence: 99%